2018
DOI: 10.1128/aac.02367-17
|View full text |Cite
|
Sign up to set email alerts
|

The Amphibian Antimicrobial Peptide Temporin B Inhibits In Vitro Herpes Simplex Virus 1 Infection

Abstract: The herpes simplex virus 1 (HSV-1) is widespread in the population, and in most cases its infection is asymptomatic. The currently available anti-HSV-1 drugs are acyclovir and its derivatives, although long-term therapy with these agents can lead to drug resistance. Thus, the discovery of novel antiherpetic compounds deserves additional effort. Naturally occurring antimicrobial peptides (AMPs) represent an interesting class of molecules with potential antiviral properties. To the best of our knowledge, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 58 publications
0
94
1
Order By: Relevance
“…Frog skin is considered an abundant source of antimicrobial peptides; however, there are still not many frog-derived peptides with antiviral activities described in the literature. They are produced in dermal glands, deployed in events of stress and, generally, present a cationic, amphipathic α-helical secondary structure, with 10-50 amino acids [86,87]. Examples are magainin 1 and 2, derived from the frog Xenopus laevis, with 23 amino acid residues each.…”
Section: Avps Derived From Amphibiansmentioning
confidence: 99%
See 1 more Smart Citation
“…Frog skin is considered an abundant source of antimicrobial peptides; however, there are still not many frog-derived peptides with antiviral activities described in the literature. They are produced in dermal glands, deployed in events of stress and, generally, present a cationic, amphipathic α-helical secondary structure, with 10-50 amino acids [86,87]. Examples are magainin 1 and 2, derived from the frog Xenopus laevis, with 23 amino acid residues each.…”
Section: Avps Derived From Amphibiansmentioning
confidence: 99%
“…The authors showed that temporin B inhibited HSV-1 in a dose-dependent manner (reaching IC50 at 2.507 µg/ml); interfered in cell-to-cell spread of the virus, suggesting that the peptide may target other cellular mechanisms used by the virus; and had virucidal action reaching 99.99% of inhibition, suggesting that the peptide acts on the viral particle. To verify the hypothesis, a TEM study was conducted and showed that virions treated with temporin B had a loss of envelope integrity [86].…”
Section: Avps Derived From Amphibiansmentioning
confidence: 99%
“…The mode of action of AMPs against bacterial cells has been extensively identified and documented; their antiviral functions were not fully understood (Skalickova et al 2015). Recent findings have suggested the efficacy of various classes of AMPs and their specific mode of action against viral pathogens and the potential use of these AMPs as an antiviral therapy (Marcocci et al 2018;Ahmed et al 2019).…”
Section: Temporinsmentioning
confidence: 99%
“…The disruption of the viral envelope was also confirmed upon observation using a transmission electron microscopy. Further, the TB was found to disturb the HSV-1 life cycle in different phases, including the attachment, entry into the host cell, and post-infection stage (Marcocci et al 2018).…”
Section: Sequence and Its Physicochemical Propertiesmentioning
confidence: 99%
“…The antiviral activity of eggplant extracts, DR2 B and DR2 C, was evaluated by plaque reduction and standard plaque assays as previously described in Marcocci et al [12]. Briefly, to perform a plaque reduction assay, Vero cells grown in 24-well plate were infected with HSV-1 at 1 m.o.i.…”
Section: Determination Of Viral Yieldsmentioning
confidence: 99%